State of the art of comprehensive repair for damage to victims women in Mexico - Ocampo Muñoa, Manuel Gustavo (2023)
This document addresses the state of the art of comprehensive reparation for damage forwomen in Mexico in order to demonstrate the level of protection that the institution screated for this purpose provide to the victims, taking into account the defense and protection approach of the rights and freedoms of the Regional Human Rights System.